Remarks at World Bank Integrity Day - McCarthy, Leonard; Zoellick, Robert B.; Volcker, Paul; Okonjo-Iweala, Ngozi (World Bank, Washington, DC, 2019)
Robert B. Zoellick, President the World Bank Group, discussed the launch of this very important event–a day of initiatives that recognize the value of integrity, governance, and anti-corruption work to the institution to build an inclusive and sustainable globalization. The Volcker Report ended up being extremely valuable by doing the "wiring diagram," to have some sense of how integrity relates to the Regions, how we relate to the donors, how we relate to clients, how we connect this to the Board, all in a way that makes this an effective process. We have 16 of the Volcker Report’s 18 recommendations in the process of being implemented.